Peran Pemerintah Terhadap Kasus Hak Asasi Manusia ( HAM) Masyaraka Papua Pegunungan - Arif Sofyan, Arif Sofyan; pramesti, Adellia putri (Equality Before The Law, 2024)
Abstract This research aims to find out how human rights law is enforced in Highland Papua and the role of Law no. 26 of 2000 in enforcing human rights. Using normative juridical research methods, it can be concluded: 1. The role of Law no. 26 of 2000 concerning the Human Rights Court in enforcing human rights law, there must be strong legal justice, no welfare of the people and protection of human rights for the Papuan people. 2. Formulation of obligations regarding the Indonesian government regarding human rights violations committed by the Armed Criminal Group (KKB) in Papua. 3. In cases of serious human rights violations committed by the KKB in Papua, the government has obligations based on Articles 71 and 72 of Law Number 39 of 1999 concerning Human Rights, namely that the state is responsible for upholding, protecting, providing, respecting and promoting human rights. If human rights violations occur, the state, as the main actor, must make law enforcement efforts to then enforce law and human right Keywords: Government Role; Human rights ; Papuan people.